Glanzmann thrombasthenia-A not so rare platelet function disorder in Pakistan - Rafia Mahmood; Hamid Saeed Malik; Maria Khan; Sadia Ali; Asad Mahmood; Saleem Ahmed Khan (Elsevier, 2022)
Objectives: To determine the prevalence, clinical manifestations and laboratory findings of Pakistani Glanzmann Thrombasthenia patients and to assess the treatment received by these patients. Materials and Method: This cross-sectional study examined 2542 patients over a period of 10 years who were referred with a suspicion of a platelet function disorder. Clinical details, laboratory parameters and treatment received were noted. Results: Glanzmann thrombasthenia constituted 80.15% of the platelet function disorders. Of these, males were 112 (34.25%) while females were 215 (65.75%). Median age at diagnosis was 9 yrs 2 months (range of 8 months to 26 years) and at first presentation was 4 years 3 months (range of 3 months to 12 years). Consanguinity was observed in 85.32% of the patients. Common clinical features were easy bruisability (85%), epistaxis (78.6%) and gum bleed (56.3%). Mean haemoglobin was 8.6+2.46 g/dl and mean bleeding time was > 15 min. All patients showed no aggregation with collagen, ADP and epinephrine and a normal response to ristocetin on light transmission aggregometry. Conclusion: We have reported a large number of patients of Glanzmann thrombasthenia, a disorder which is not so rare in our population, emphasizing the importance of early diagnosis and appropriate management.